2012
DOI: 10.1111/j.1365-2044.2012.07337.x
|View full text |Cite
|
Sign up to set email alerts
|

The analgesic efficacy and safety of neuraxial magnesium sulphate: a quantitative review

Abstract: SummaryEighteen published trials have examined the use of neuraxial magnesium as a peri-operative adjunctive analgesic since 2002, with encouraging results. However, concurrent animal studies have reported clinical and histological evidence of neurological complications with similar weight-adjusted doses. The objectives of this quantitative systematic review were to assess both the analgesic efficacy and the safety of neuraxial magnesium. Eighteen trials comparing magnesium with placebo were identified. The ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 47 publications
1
58
0
2
Order By: Relevance
“…For many years, animal studies suggested that intrathecal magnesium was able to block acute pain and hyperalgesia after surgery. Recent reviews of the literature in humans showed that intrathecal magnesium does allow for an interesting decrease in postoperative acute pain, 50 but intravenous magnesium was less potent. 51 The fact that intravenous magnesium was less convincing to decrease acute postoperative pain might be explained by one clinical trial from Mercieri et al 52 In their study, the authors reported that intravenous magnesium did not properly cross the blood-brain barrier and, thus, could hardly be expected to decrease acute postoperative pain if this effect relied on its activity at the CNS level.…”
Section: Ketaminementioning
confidence: 99%
“…For many years, animal studies suggested that intrathecal magnesium was able to block acute pain and hyperalgesia after surgery. Recent reviews of the literature in humans showed that intrathecal magnesium does allow for an interesting decrease in postoperative acute pain, 50 but intravenous magnesium was less potent. 51 The fact that intravenous magnesium was less convincing to decrease acute postoperative pain might be explained by one clinical trial from Mercieri et al 52 In their study, the authors reported that intravenous magnesium did not properly cross the blood-brain barrier and, thus, could hardly be expected to decrease acute postoperative pain if this effect relied on its activity at the CNS level.…”
Section: Ketaminementioning
confidence: 99%
“…Nevertheless, IT magnesium has been used in significant number of humans and there have been no documented neurological complications. [16] Onset of analgesia at T6 was delayed with intrathecal magnesium sulphate compared to intravenous magnesium and placebo. Time to 2 segment regression of sensory block, duration of spinal anaesthesia as well as duration of effective analgesia were significantly prolonged in intrathecal as well as intravenous magnesium as compared to placebo.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15] However, IT magnesium has been used in significant number of humans and there were no documented neurological complications. [16] Histopathological and ultra-structural human spinal cord studies may sound interesting but are practically next to impossible. In such circumstances off label use of magnesium intrathecally is supposed to thrive because of its advantages.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of rescue analgesic was also significantly less on addition of magnesium sulphate (p<0.01) Albrecht et al 15 in their review found that the time for first analgesic request increased by 11.1% after intrathecal magnesium administration and by 72.2 % after epidural administration with doses between 50 and 100mgs.…”
Section: Variablementioning
confidence: 99%